Effect of childhood trauma on substance users’ attitudes of coping with stress - Orak, Oya Sevcan; Bilkay, Halil İbrahim and Zengin, Çiğdem (Journal of Dependence, 2023)
Objective: This study seeks to examine the effects of childhood traumas on substance users’ attitudes of coping with stress. Method: This descriptive study seeking relationship was conducted with 133 individuals diagnosed with substance use and receiving treatment in the alcohol and substance treatment centre and closed psychiatry clinics of a mental health hospital located in Turkey. Results: The mean age of first substance use of the participants included in the study was 17.8 ± 4.7. The participants got the highest score from the emotional neglect subscale of the Childhood Trauma Questionnaire (12.83 ± 3.46). Individuals in the study got the highest score from the religious coping subscale of the Coping Orientation to Problems Experienced Inventory (13.39 ± 2.71). Childhood traumatic experiences were found to be effective in the development of coping attitudes including denial, behavioural disengagement, use of emotional social support, substance use, and acceptance. Conclusion: Childhood traumatic experiences of substance users have an effect on their dysfunctional coping attitudes. It is recommended that psychiatric nurses include primary, secondary, and tertiary protective approaches towards childhood traumas in their work on combating addiction.